Pengaruh Kualitas Pelayanan dan Harga Terhadap Loyalitas Pelanggan di PT Pos Indonesia Cabang Leles - Luthvia Azzahra; Wawat Setiawati (Jurnal Ilmiah Manajemen, Bisnis dan Kewirausahaan, 2026)
The rapid growth of e-commerce in Indonesia has led to an increasing demand for reliable and competitive delivery services. This condition has intensified competition within the logistics industry, including for PT Pos Indonesia Leles Branch. However, internal data and a preliminary survey indicate a decline in the number of customers, suggesting potential issues related to service quality and pricing that may affect customer loyalty. This study aims to analyze the effect of service quality and price on customer loyalty at PT Pos Indonesia Leles Branch. This research employs a quantitative approach using a survey method. Data were collected through questionnaires distributed to customers of PT Pos Indonesia Leles Branch. The data were analyzed using descriptive analysis and verificative analysis with multiple linear regression, as well as t-tests and F-tests to examine the partial and simultaneous effects of the independent variables on customer loyalty. The results indicate that service quality and price have a positive and significant effect on customer loyalty, both partially and simultaneously. These findings suggest that improving service quality while offering competitive and reasonable pricing can enhance customer loyalty. This study is expected to contribute theoretically to service marketing literature and provide practical insights for PT Pos Indonesia in formulating effective strategies to strengthen customer loyalty.